Endoscopic or Follow-up Treatment for Gastric Indeterminate Tumors Is the Preferred Method of Management - Xiao, Jun; Yu, Chao; Chen, Jing; Sun, Renhu; Jin, Hailin; Liu, Chunyang; Wang, Yaohui; Sun, Zhiguang (Frontiers in Oncology, 2022)
Background Endoscopic forceps biopsy (EFB) lacks precision in diagnosing indeterminate tumors. When the presence of early gastric cancer (EGC) is macroscopically suspected, but biopsy pathology fails to give a diagnosis of neoplasia, it causes problems in clinical management. The purpose of this study was to discuss the outcome of gastric indeterminate tumors and the clinical factors associated with predicting EGC. Methods The medical records of 209 patients diagnosed with gastric indeterminate neoplasia by biopsy forceps were retrospectively studied. Initial endoscopic findings were analyzed and predictors of EGC were evaluated. Results The final pathological diagnosis in 209 patients included adenocarcinoma (n = 7), high-grade intraepithelial neoplasia (n = 11), low-grade intraepithelial neoplasia (n = 21), and non-neoplastic lesion (n = 170). Multivariate analysis showed that older age (OR = 1.78; 95% CI = 1.17–2.71; p = 0.008), patients undergoing narrow band imaging (NBI) (OR = 3.40; 95% CI = 1.37–8.43; p = 0.008), and surface erosion (OR = 3.53; 95% CI = 1.41–8.84; p = 0.007) were associated with the upgraded group, and were significantly associated with risk. Univariate logistic regression analysis showed that among patients with NBI, the presence of demarcation line (DL) (OR = 24.00; 95% CI = 4.99–115.36; p < 0.0001), microvascular (MV) pattern irregularity (OR = 9.129; 95% CI = 2.36–35.34; p = 0.001), and the presence of white opaque substance (WOS) (OR = 10.77; 95% CI = 1.14–101.72; p = 0.038) were significant risk factors. Conclusions For gastric indeterminate tumors, older patient age, lesion surface with erosion, clear DL visible under NBI observation, presence of WOS, and irregular MV pattern are suggestive of the high possibility of neoplasia and need to be focused on and may benefit more from endoscopic resection treatment as opposed to simple endoscopic follow-up.